Ultrasound-guided subacromial–subdeltoid bursa corticosteroid injections: a study of short- and long-term outcomes. Issue 8 (August 2018) - Fawcett, R.; Grainger, A.; Robinson, P.; Jafari, M.; Rowbotham, E.
Abstract : Aim: To assess shoulder pain and disability in patients undergoing corticosteroid injection into the subacromial–subdeltoid (SA-SD) bursa under ultrasound guidance, evaluating both short and long-term outcomes. Materials and methods: In this prospective, longitudinal, analytical study 376 patients referred for SA-SD bursa injection during a 6 month period were asked to complete a questionnaire assessing shoulder pain and disability in the form of the Shoulder Pain and Disability Index (SPADI). Patients were reassessed at 6 weeks and 12 months post-injection. Data were collated and analysed based on the diagnosis made at ultrasound. Results: Almost two-thirds (63.6%) of patients irrespective of the underlying diagnosis showed improvement in pain and disability 6 weeks after injection, but this figure decreased significantly after 12 months to 27.3%. There was no significant difference in outcome between patients with a rotator cuff tendon tear and without a tear at 6 weeks; however, there was a difference between these two groups at 12 months with significantly fewer patients with a tear receiving benefit. Conclusion: The pattern of good short-term, but poorer long-term outcomes from SA-SD bursa injection is in line with previous studies; however, this study provides additional information on the effect of the underlying diagnosis on the potential outcome, specifically the presence or absence of a rotator cuff tendon tear. Highlights: Ultrasound-guided subacromial-subdeltoid bursa corticosteroid injection offers a significant improvement in pain and disability in 64% of patients in the short-term (after 6 weeks). Fewer patients (27%) gain long-term improvement. If a rotator cuff tear is present there is very unlikely to be long-term benefit, however, a small proportion (31%) will gain short-term relief. If there is tendon or bursal pathology without a tear there is no significant difference in outcome according to the underlying diagnosis.